UCT943, a next generation plasmodium falciparum PI4K inhibitor preclinical candidate for the treatment of malaria - Brunschwig, C; Lawrence, N; Taylor, D; Abay, E; Njoroge, M; Basarab, GS; Le Manach, C; Paquet, T; Cabrera, D; Nchinda, AT; de Kock, C; Wiesner, L; et al. (American Society for Microbiology, 2018)
The 2-aminopyridine MMV048 was the first drug candidate inhibiting Plasmodium phosphatidylinositol 4-kinase (PI4K), a novel drug target for malaria, to enter clinical development. In an effort to identify the next generation of PI4K inhibitors, the series was optimized to improve properties such as solubility and antiplasmodial potency across the parasite lifecycle, leading to the 2-aminopyrazine UCT943. The compound displayed higher asexual blood stage, transmission-blocking, and liver stage activity than MMV048 and was more potent against resistant P. falciparum and P. vivax clinical isolates. Excellent in vitro antiplasmodial activity translated into high efficacy in P. berghei and humanized P. falciparum NOD-scid IL-2Rγnull mouse models. The high passive permeability and high aqueous solubility of UCT943, combined with low to moderate in vitro intrinsic clearance, resulted in sustained exposure and high bioavailability in preclinical species. In addition, the predicted human dose for a curative single administration using monkey and dog pharmacokinetics was low, ranging from 50 to 80 mg. As a next generation Plasmodium PI4K inhibitor, the combined preclinical data suggest that UCT943 has the potential to form part of a single-exposure radical cure and prophylaxis (SERCaP) to treat, prevent and block the transmission of malaria.